The Students' Interest in Modified 'Gelang Dewa' Media for Discus Throw Learning (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aims to examine students' interest in the use of "Gelang Dewa" learning media innovations in the topic of discus throwing in Physical Education, Sports, and Health (PJOK) lessons. This innovation was created as a creative step to overcome the limitations of standard facilities and difficult school infrastructure conditions. The methodology applied was a quantitative descriptive survey with an associative approach. The research subjects consisted of 100 grade VIII students at MTsN Surakarta 1, with a sample taken of 30 students through purposive sampling techniques. Data were obtained using a closed questionnaire with a Likert scale that has been tested to be valid and reliable (Cronbach's Alpha = 0.743). The results of descriptive statistical analysis showed that student interest was at a high level, with an average score of 73.20. These findings show that the use of “Gelang Dewa” has a significant impact on increasing students' active participation, reducing anxiety about injuries, and reducing physical fatigue during learning. The use of this ergonomically designed and adaptive tool has proven effective in increasing situational interest and supporting the mastery of basic discus throwing techniques in a more inclusive manner. This study concludes that the development of creative tools from teachers is an important factor in overcoming facility constraints in order to maximize students' moving experience and physical participation in the school environment.